1990
DOI: 10.1042/bj2680225
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin gene expression by endothelial cells in culture is modulated by cell proliferation, cell shape and the substratum

Abstract: Endothelial cells plated on the surface of a two-dimensional substratum (gelatin-coated dishes, dishes coated with native type I collagen or collagen gels) form a cobblestone monolayer at confluence, whereas cells plated within a threedimensional gel matrix elongate into a sprouting morphology and self-associate into tube-like structures. In this study, we have compared the synthesis of thrombospondin by quiescent endothelial cells displaying (a) the same morphological phenotype (cobblestone) on different subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 41 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…Since endothelial cells that are incorporated into tubes tend to be less active mitotically than the population from which they are derived (6)(7)(8), these findings are consistent with earlier data indicating an inverse relationship between the rate of growth and TSP production by endothelial cells in culture (29). The findings are also consistent with the more recent studies of Canfield et al (30), who reported that the level of TSP synthesis by BAEC correlated more precisely with cell shape than with rate of growth. In particular, these workers showed that BAEC cultured within collagen gels, a condition that promoted an elongated morphology similar to that displayed by sprouts, produced low levels of TSP mRNA and protein, regardless of the proliferative state of the cells.…”
Section: Discussionsupporting
confidence: 83%
“…Since endothelial cells that are incorporated into tubes tend to be less active mitotically than the population from which they are derived (6)(7)(8), these findings are consistent with earlier data indicating an inverse relationship between the rate of growth and TSP production by endothelial cells in culture (29). The findings are also consistent with the more recent studies of Canfield et al (30), who reported that the level of TSP synthesis by BAEC correlated more precisely with cell shape than with rate of growth. In particular, these workers showed that BAEC cultured within collagen gels, a condition that promoted an elongated morphology similar to that displayed by sprouts, produced low levels of TSP mRNA and protein, regardless of the proliferative state of the cells.…”
Section: Discussionsupporting
confidence: 83%
“…TSP1 expression in endothelial cells is also regulated by cell-cell contact (Mumby et al, 1984;Canfield et al, 1990). Cells without mature cell-cell contacts produce more TSP1 than confluent cells (Mumby et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…15 This large difference in production rates is consistent with a study of endothelial cell production of thrombospondin in 2D and 3D collagen-based cultures (no flow) in which the production rates were observed to be much higher in 2 than in 3 dimensions. 16 A related study of rabbit arterial SMCs in 2D and 3D collagen-based cultures (no flow) showed that the cell growth rate was greatly inhibited in 3D cultures relative to 2D cultures. 17 It seems that cells in 3 dimensions are in a more quiescent state than cells in 2 dimensions in terms of both growth rate and biochemical activity.…”
Section: Discussionmentioning
confidence: 99%